Ryanodine receptor mutations (G4946E and I4790K) differentially responsible for diamide insecticide resistance in diamondback moth, Plutella xylostella L. (March 2020) - Jouraku, Akiya; Kuwazaki, Seigo; Miyamoto, Kazuhisa; Uchiyama, Makoto; Kurokawa, Tatsuki; Mori, Emiko; Mori, Masayuki X.; Mori, Yasuo; Sonoda, Shoji
Abstract: This study examined diamondback moth ( Plutella xylostella ) strains showing high-level resistance to cyantraniliprole (KA17 strain) and to flubendiamide and chlorantraniliprole (KU13 strain). The LC50 value of the KA17 strain against cyantraniliprole was ca. 100-fold higher than that of the KU13 strain. The KA17 strain also exhibited high-level resistance to chlorantraniliprole and flubendiamide equivalent to those in the KU13 strain. The KU13 strain showed a higher LC50 value against cyantraniliprole than the susceptible strains. However, the LC50 value of the KU13 strain against cyantraniliprole was below the agriculturally recommended concentration. Subsequent QTL analysis using ddRAD-seq identified the resistance responsible regions of the KA17 and KU13 strains with different diamide resistance profiles. Ryanodine receptor (RyR) gene was included in the identified regions. Single nucleotide polymorphism calling in the RyR gene using RNA-seq found previously reported G4946E (amino acid mutation from glycine to glutamic acid at amino acid position 4946) and novel I4790K (amino acid mutation from isoleucine to lysine at amino acid position 4790) mutations, respectively, in the RyR of the KU13 and KA17 strains. Functional significance of I4790K in the resistance was confirmed in calcium imaging of the human embryonic kidney 293T cell line expressing Bombyx mori RyR with the mutation. This reporting is the first describing I4790K as a fundamental mechanism responsible for the resistance to the diamides including cyantraniliprole. From this study, we also report up-regulated expression of some degradation enzymes and that of the RyR gene in the KA17 and KU13 strains based on results of RNA-seq data analysis. Graphical abstract: Image 1 Highlights: QTL analysis of Plutella xylostella strains was done using ddRAD-seq. Resistance-responsible regions were flubendiamide G4946E and cyantraniliprole I4790K. P. xylostella (I4790K) resist flubendiamide, chlorantraniliprole and cyantraniliprole. Human cells expressing Bombyx mori RyR with the mutation confirmed effects of I4790K. RNA-seq analysis identified some up-regulated genes in diamide-resistant strains.